The reliability of cephalometric measurements in oral and maxillofacial imaging: Cone beam computed tomography versus two-dimensional digital cephalograms - Arvind Hariharan; N R Diwakar; K Jayanthi; H M Hema; S Deepukrishna; Snehal R Ghaste (Wolters Kluwer Medknow Publications, 2016)
Context: This study compared digital two-dimensional (2D) lateral cephalograms and cone-beam computed tomography (CBCT) total and half-skull images for the reliability of cephalometric measurements. Aims: (1) To compare the accuracy of cephalometric measurements and reproducibility between the digital and CBCT cephalograms in the Indian population. (2) To compare interobserver variability in landmark identification through their cephalometric measurements by comparing different imaging modalities (CBCT total skull, CBCT half-skull, and conventional lateral cephalogram). (3) To further compare half-skull with the total skull synthesized CBCT and digital cephalograms in the same regard. Materials and Methods: Thirty patients, who had consented with orthodontic treatment, participated in the study. Informed consent was obtained from the patient before the radiographic procedures. 2D digital lateral cephalograms and their corresponding CBCT scans were taken and imported in DICOM format to OnDemand 3D software. Twenty-three landmarks were identified by 3 observers and 9 linear and 14 angular measurements were digitally traced. The values were sent for statistical analysis using ANOVA to check the interobserver reliability between the imaging modalities. Statistical Analysis Used: ANOVA, Student's t-test, and post hoc test were used for the statistical analysis. Results: The interobserver reliability was high between the modalities. CBCT total skull received an overall intraclass correlation coefficient (ICC) value of 0.76. The ICC value for the CBCT half-skull was 0.79 and for the digital cephalograms it was 0.80. The reliability for CBCT total skull was marginally less when compared to the CBCT half-skull and digital cephalograms, but more for the mid-sagittal measurements. Digital cephalograms showed the most variation with measurements of the mandibular plane when compared to CBCT. Conclusions: CBCT has the potential to be used for cephalometrics, especially the half-skull images, but further studies are required to prove whether CBCT total skull images can be used. 2D cephalometry, however, still does remain as the mainstay of orthodontic diagnosis and treatment planning and cannot be easily replaced by three-dimensional cephalometry.